Rooftop rainwater harvesting and artificial groundwater recharge - a case study: Thanh Xuan district in south of Hanoi - Tran Thi, Luu; Nguyen Thi Thu , Hien (Vietnam Journal of Earth Sciences, 2022)
Groundwater over-exploitation in the south of Hanoi has formed depression cones and accelerated land subsidence. Thanh Xuan district is one of the most suffered areas in the south of Hanoi. Artificial groundwater recharge (AGR) is an effective solution to mitigate those negative impacts. This study aims to evaluate the potential of rooftop rainwater harvesting (RRH) for AGR in the Thanh Xuan district. The prospect of RRH for the study area is estimated based on the average annual rainfall for the period 2008-2018 and the total rooftop area of selected buildings. The rooftop area is determined by analyzing satellite images and using the built-in tool in Google Earth. Field site investigation and measurements confirmed this estimation. Rainwater samples were taken for quality assessment. This assessment was conducted by measuring pH, EC, TDS, turbidity of rainwater in the field and analyzing NO3-, NO2-, PO43-, SO42- and Cl- contents in the laboratory. Moreover, to propose an effective AGR system, the maximum harvested rainwater and the recharge capacity of an injection well were estimated for the Golden Land building. The results show that 397 selected buildings can be used to collect rainwater. The total rooftop area of these 397 buildings is 262,645.8 m2, and that can contain 385,930.5 m3 of rainwater a year. The field measurement and analysis results indicate that rainwater quality meets the current standards appropriate for AGR. The AGR using rooftop rainwater will contribute to increasing groundwater level, reducing land subsidence, and mitigating urban flooding for Thanh Xuan and similar areas.